2006
DOI: 10.3844/ajidsp.2006.141.152
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and Adiponectin in the HIV Associated Metabolic Syndrome: Physiologic and Therapeutic Implications

Abstract: Leptin and adiponectin represent two newly discovered adipose tissue derived hormones with important roles in energy homeostasis and insulin resistance. Their interrelations with the manifestations of the HIV associated metabolic syndrome and specific somatomorphic changes i.e. fat redistribution is reviewed. A synopsis of published studies is presented and the potential role of leptin and adiponectin is discussed. We have described an association of the HIV metabolic syndrome with a state of reduced insulin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 148 publications
(160 reference statements)
1
33
0
Order By: Relevance
“…35 Adipokines are dysregulated in HIV-infected persons. [36][37][38] Lean HIV-positive, ART-treated men had adiponectin levels similar to obese, insulin-resistant HIV-negative men, and those with extremity fat loss had even lower levels. 36 Baseline trunk and limb fat by DEXA did not differ by m.10398 allele in our analyses (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…35 Adipokines are dysregulated in HIV-infected persons. [36][37][38] Lean HIV-positive, ART-treated men had adiponectin levels similar to obese, insulin-resistant HIV-negative men, and those with extremity fat loss had even lower levels. 36 Baseline trunk and limb fat by DEXA did not differ by m.10398 allele in our analyses (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-associated lipoatrophy is a much more prevalent condition, affecting an estimated 15-36% of HIV-infected patients (120) and is closely linked with insulin resistance and dysregulation of peripheral adipose tissue metabolism (159,235,262). In our initial randomized, placebo-controlled, interventional study, we found that leptin in physiological doses improves insulin resistance, hyperlipidemia, and truncal fat mass in these patients (23,141).…”
Section: Lipodystrophymentioning
confidence: 93%
“…Leptin and adiponectin have both been implicated in combined antiretroviral therapy (cART)-related lipodystrophy and metabolic syndrome. 22,23 Leptin deficiency is associated with lipoatrophy, while low levels of adiponectin are associated with central fat accumulation and insulin resistance. 22 In addition to affecting metabolic pathways that lead to changes in fat distribution, leptin, and adiponectin also influence immune pathways that may both modulate HIV disease and influence BM responsiveness.…”
Section: Introductionmentioning
confidence: 99%